2019
DOI: 10.1039/c9sc02227a
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the radical-induced redox chemistry inside a liquid-cell TEM

Abstract: A holistically described radical-induced redox chemistry modelling allows for a direct assessment of the in situ experiments inside a liquid-cell TEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 39 publications
(64 reference statements)
1
49
1
Order By: Relevance
“…[11,12] Vavra et al [11] revealed dissolution/redeposition as the main degradation mechanism in the initial stages of ERC. Nevertheless, the insitu liquid TEM with all its limitations (e. g., beam-induced radiolysis effects) [23,24] provides only low-resolution morphological changes of the of Cu-based catalyst. Even though the exsitu characterization cannot probe the nature of catalytic sites, [14] it is still common and very useful to observe and follow morphological changes.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Vavra et al [11] revealed dissolution/redeposition as the main degradation mechanism in the initial stages of ERC. Nevertheless, the insitu liquid TEM with all its limitations (e. g., beam-induced radiolysis effects) [23,24] provides only low-resolution morphological changes of the of Cu-based catalyst. Even though the exsitu characterization cannot probe the nature of catalytic sites, [14] it is still common and very useful to observe and follow morphological changes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Interestingly, the dynamics of colloidal assemblies composed of several hundred nano‐objects can be monitored to extract statistical information on the nucleation and growth processes [ 6 ] and the chemical reactions can also be observed at the single NP level to provide in situ insights into the atomic‐scale mechanisms driving NP size and shape. [ 7 ] However, as the use of LCTEM with temperature control is very recent, [ 8 ] the direct observations of thermal effects on the formation processes of nanomaterials are still in their infancy.…”
Section: Introductionmentioning
confidence: 99%
“…can be produced in water by high energy electron beam irradiation and the etching mechanisms in LCTEM are very complicated. [ 14–17 ] ZnO is an amphoteric oxide which can be etched in deionized water (pH ≈ 6.7–6.9), ambient environment, H 2 O 2 , acid, and alkali solution. [ 18–22 ] Hence, most radicals (H 2 O 2 , H 3 O + , OH•, HO 2 •,etc.)…”
Section: Figurementioning
confidence: 99%